Nutritionism, Commercialization and Food; Comment on "Buying Health: The Costs of Commercialism and an Alternative Philosophy" - Anne Barnhill (Kerman University of Medical Sciences, 2013)
In "Buying Health: the Costs of Commercialization and an Alternative Philosophy", Larry R. Churchill and Shelley C. Churchill discuss the commercialization of health and, in particular, the commercialization of nutrition. In this commentary on their article, I draw a connection between Churchill and Churchill's account of the commercialization of nutrition and Michael Pollan's critique of "nutritionism". I also offer a friendly amendment to Churchill and Churchill's account, suggesting that the commercialization of nutrition is not a monolithic experience but it is rather widely challenged.